Cooperative Learning Dalam Bahasa Arab: Metode Belajar di MA Nurul Huda - Satriadi satriadi satriadi; Muassomah (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2021)
The paper elaborates about the application of Arabic learning with the Cooperative Learning method, along with the results obtained after applying this method to 11 students of class XI MA Nurul Huda Pandan Jaya. This research used a qualitative descriptive approach with observation, interview and documentation research instruments. The results showed that the applied Cooperative Learning method is able to affect student’s outcomes, besides that students are more motivated to think more critically in solving problems in the form of discussions, and are more courageous to express their arguments both in their groups and to deliver to the class.